The Effect of Breast Care on Decreasing the Scale of Breast Milk Swelling in Postpartum Mothers at Pera Clinic, Medan City - Desriati Sinaga; Risda Mariana Manik (Science Midwifery, 2022)
Breast milk dams occur due to increased venous and lymph flow, causing breast milk damming and pain accompanied by an increase in body temperature. Breast care is done as an effort to reduce the dam of breast milk. This study aims to analyze the effect of breast care on decreasing the scale of breast milk engorgement. The design in this study was a quasi-experimental (one group pretest and posttest) which was conducted on 31 postpartum mothers with breast milk dams at Pera Clinic, Medan City. The results of the study obtained a p value of 0.000 (p <0.05) so it can be concluded that there is a significant difference in the decrease in the scale of the swelling of the breast milk dam before and after breast care.